EFFECT OF PEPPERMINT (MENTHA PIPERITA) POWDER ON PERFORMANCE, GUT MORPHOLOGY AND IMMUNE ORGANS RESPONSE OF COCCIDIOSIS INFECTED BROILERS - Hussein, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This experiment was performed to find out the effect of peppermint on the performance, gut morphology and immune organs of coccidiosis challenged broilers. A feeding trail was conducted on 320-day-old Ross 308 chicks allocated to 32 floor pens in a 2x4 factorial arrangement. The studied factors were: challenge (Negative or Positive) and feed additive (Control, Peppermint and). On day 8 of age, birds in challenged groups were orally inoculated with Eimeria tenella. On day 35 Eimeria decreased weight (P